The influence of information on residents’ green housing purchasing behavior: different information contents and providers - He, Chenchen; Liu, Xuan; Bi, Jiahui; Wang, Xiaohua; Li, Jiaxin (Journal of Civil Engineering and Management, 2023)
To promote consumers to buy green housing, the paper tries to find the effect of information on consumers’ green housing purchasing behavior. It classifies the contents and providers of information and explores their different influences. The results show that: 1) Consumers’ age and environmental protection attitude have a significant impact on their purchasing behavior, while consumers’ gender and monthly income have no significant impact; 2) Consumers are more affected by information relating to the economy and indoor air quality. The detailed order of influence is as follows: information on loan at concessionary rates > cost saving in usage phase > indoor air quality > waste classification > investment benefit > carbon emission reduction > thermal comfort > acoustic environment > greening rate > luminous environment; 3) Consumers with higher environmental awareness care more about the information on living environment and carbon emission. Whereas, those with low awareness of environmental protection are more affected by information on economic benefits. 4) Regarding different information providers, the consumers are mostly impacted by the government, while the information from developers could induce limited effects. It could guide the government and developers to provide appropriate information to promote GH purchasing behavior.